10.1016/s0029-7437(11)70065-9 (CrossRef Listing of Deleted DOIs, 2000)
Published data on flow cytometric assessment of Classic Hodgkin lymphoma (CHL) are largely limited to lymph node biopsies, where histopathological and immunophenotypic findings are already available, thereby restricting its practical applicability. Real-world evidence demonstrating the additional diagnostic role of flow cytometric immunophenotyping (FCI) in CHL is limited. This study evaluated the utility of FCI in body fluids (BF) and bone marrow samples submitted for the diagnostic evaluation and staging of CHL in routine clinical practice. We studied 126 samples from 120 patients evaluated for CHL diagnosis or staging, including fine-needle aspirates (FNAs, n = 15), tissue biopsies (n = 6), bone marrow aspirates (BMAs, n = 76), and BF (n = 29). Samples were processed using a lyse-stain-wash protocol, acquired on BD-LSRFortessa, and analyzed using Kaluza software. A single-tube 16-color antibody panel (CD3, CD11b, CD13, CD15, CD19, CD20, CD30, CD33, CD38, CD40, CD45, CD64, CD71, CD73, CD95, and CD271) was used. The findings were correlated with the clinical, histopathological, and immunohistochemical data. CHL involvement was detected in 13 samples (5 FNAs, 5 fluids, 2 BMAs, 1 lymph node). The level of Hodgkin and Reed-Sternberg cells (HRS) ranged from 0.03% to 2.86% (median, 0.43%) in positive samples. HRS cells consistently expressed CD30, CD40, CD71, and CD95. FCI demonstrated excellent sensitivity and specificity in fluids, FNA, and core needle biopsy; however, it exhibited poor sensitivity in BMA, likely due to hemodilution or non-representative sampling. FCI complements histopathology by enabling the rapid and accurate detection of CHL involvement, particularly in BF and limited tissue samples such as FNA and small biopsies.